Bilingual children access multiplication facts from semantic memory equivalently across languages: Evidence from the N400 - Cerda, Vanessa R. (Brain Lang, 2019)
Typically, bilinguals learn multiplication facts in only one instruction language. Consequently, these facts may be represented and/or accessed as language-specific memories, requiring a qualitatively different retrieval process in their other language. Indeed, behavioral studies reveal that bilinguals verify arithmetic facts faster and better in the language of learning. Here, event-related potentials (ERPs) were used as a window into the neurocognitive processes underlying this language bias in children. ERPs were recorded while bilingual children verified the correctness of multiplication solutions. Operands were presented as spoken number words in Spanish and English, separately. Although a language bias was revealed in behavior, both languages elicited the same ERP correctness effect, an N400, reflecting similar cognitive processes in both languages. This suggests that the source of the behavioral difference is not at the level of semantic access. Our findings highlight the flexibility of the bilingual brain, especially when both languages are learned early.